Analisis Dampak DER, ITO, dan Curent Ratio terhadap Return Saham dengan Variabel ROA sebagai Variabel Intervening - Hironimus Olang; Sri Hermuningsih; Gendro Wiyono (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study aims to determine the impact of Debt To Equity Ratio (Der), Inventory Turn Over (Ito), and Current Ratio to Stock Returns with Return On Asset (ROA) s (Roa) as Intervening Variables. Population and Sample The population in this study are all food and beverage companies listed on the Indonesia Stock Exchange for the 2016-2020 period according to the classification of the Indonesia Capital Market Directory. The sampling method used is non-probability sampling with purposive sampling technique. Methods of data collection in this study using the method of study documentation and literature study of companies that will be used as samples are 14 food and beverage companies. In order to perform the inferential analysis of this research, the analytical tool used is Patial Least Square (PLS), which is SEM based on variance, with SmartPLS software. Based on the results of data analysis shows that: The results of the hypothesis H1 indicate that the Debt To Equity Ratio (DER), (X1) has a negative effect on stock returns. H2 shows that the inventory turnover (ITO) (X2) has a positive effect on stock returns. The results of the hypothesis H3 show that the current ratio (CR) (X3) has a negative effect on stock returns. The results of the hypothesis H4 show that the Debt To Equity Ratio (DER) (X4) has a negative effect on Return On Asset (ROA) s ROA (z) . The results of the hypothesis H5 show that the inventory turnover (ITO) (X5) has a negative effect on Return On Asset (ROA) s ROA (z). The results of the hypothesis H6 indicate that the current ratio (X6) has a negative effect on Return On Asset (ROA) s ROA (z). The results of the hypothesis H7 show that the Return On Asset (ROA) s (X7) has a negative effect on stock returns (Y) . The value of the P-Value obtained is 0.679 which is greater than 0.05. Based on the mediation analysis, it is stated that the moderating variable (Return On Asset (ROA) s) does not significantly reduce the effect of the Debt To Equity Ratio (der) on stock returns. And the moderating variable (Return On Asset (ROA) s) does not significantly have a decreasing effect between inventory turnover and stock returns. And the moderating variable (Return On Asset (ROA) s) does not significantly have a decreasing effect between the current ratio (CR) on stock returns. Keywords: Debt To Equity Ratio (Der), Inventory Turn Over (Ito),Dan Curent Ratio Return Saham Return On Asset (ROA) (Roa)